Spatial patterns of species richness and functional diversity in Costa Rican terrestrial mammals: implications for conservation. Issue 1 (8th October 2015) - González‐Maya, José F.; Víquez‐R, Luis R.; Arias‐Alzate, Andrés; Belant, Jerrold L.; Ceballos, Gerardo
Abstract: Aim: Functional diversity is a relatively recent approach to quantify species diversity and may provide a better understanding of the linkages between biological diversity and ecosystem functioning. Understanding the relationships between mammal species richness and functional diversity, the factors that influence these relationships, and the spatial scale at which they operate, can improve our knowledge of ecosystem functioning and may benefit conservation planning. Location: Costa Rica (8°0′–11°14′N and 82°32′–85°56′W). Methods: We evaluated spatial patterns of species richness and functional diversity for terrestrial mammal species in Costa Rica using regression techniques and assessed the influence of environmental, biological and anthropogenic factors on those patterns. Results: Environmental and anthropogenic factors influenced species richness and functional diversity, while a biological factor (i.e. species' geographic origin) only influenced functional diversity. Observed patterns of species richness and functional diversity resulted in identification of three regions which could be differentiated by ecosystem type and the occurrence of bats and rodents. The spatial scale at which variation in these diversity measures also differed, with species richness most affected at fine spatial scales (local) and functional diversity best explained at the meso‐scale (regional level). Main conclusions: Both diversity measures varied spatially in relationship of examined factors, and the extent at which influencing factors affect both measures also varied across the country and scales. Our results highlight that investigating the interaction of scales is necessary for also further understanding macroecological patterns. Considering multiple measures of biological diversity and the spatial scales at which they operate may improve our understanding of biodiversity and the efficacy of species and community conservation planning.